Research on resting spontaneous brain activity and functional connectivity of acupuncture at uterine acupoints - Yuan Hang; Yu Xiaohua; Li Xiang; Qin Sijun; Liang Guixiang; Bai Tianyu; Wei Benzheng (KeAi Communications Co., Ltd., 2022)
Objective: The resting-state functional magnetic resonance imaging (rs-fMRI) method was used to observe brain activity and its functional connection upon electroacupuncture stimulation at bilateral uterine acupoints (EX-CA1), as well as to investigate the mechanism of acupuncture in the treatment of gynecological diseases. Methods: Twenty-two healthy female subjects were stimulated by electroacupuncture at bilateral uterine acupoints; rs-fMRI data of the brain were acquired and standardized. Degree centrality (DC), amplitude of low-frequency fluctuation (ALFF), and regional homogeneity (ReHo) were used to analyze local spontaneous brain activity via acupuncture. An independent component analysis was used to evaluate the functional connectivity of the resting brain networks after acupuncture. Results: Analytical results showed that the neural activity intensity of the precuneus lobe, orbitofrontal cortex, lingual gyrus, amygdala, and posterior central gyrus decreased after acupuncture (voxel P < 0.001, cluster P < 0.05). Functional connectivity analysis revealed weakened auditory and right frontal-parietal networks (voxel P < 0.001, cluster P < 0.05), enhanced visual network (voxel P < 0.001, cluster P < 0.05), and synergistic auditory network and hypothalamic-pituitary system. Conclusion: Significant differences in neural activity and functional connectivity in specific brain regions were observed after acupuncture intervention at uterine acupoints; the hypothalamic-pituitary system also showed various active states in different brain regions. It is speculated that the effective mechanism of acupuncture at uterine acupoints is related to the regulation of reproductive hormones, emotional changes, and somatic sensations. Therefore, the methods used in this study could clarify the neural mechanism of uterine-point acupuncture in the treatment of gynecological diseases and may serve as a reference for other studies pertaining to acupuncture.